2015
DOI: 10.1158/1078-0432.ccr-14-2027
|View full text |Cite
|
Sign up to set email alerts
|

β-Cryptoxanthin Synergistically Enhances the Antitumoral Activity of Oxaliplatin through ΔNP73 Negative Regulation in Colon Cancer

Abstract: Background: The acquired resistance to chemotherapy represents the major limitation in the treatment of cancer. New strategies to solve this failure and improve patients' outcomes are necessary. The cancer preventive effect of b-cryptoxanthin has been widely described in population studies. Few reports support its putative use as an antitumoral compound. Here we focus on the therapeutic potential of b-cryptoxanthin individually or in combination with oxaliplatin in colon cancer and try to decipher the molecula… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 41 publications
(20 citation statements)
references
References 52 publications
0
20
0
Order By: Relevance
“…A very recent human intervention study [ 62 ] focused on the therapeutic potential of β-cryptoxanthin individually and in combination with oxaliplatin in colon cancer: β-cryptoxanthin decreased the proliferation of cancer cells and cooperated with oxaliplatin to induce apoptosis through the negative regulation of NH 2 -terminally truncated p73 (ΔNP73). The administration of anti-tumoral drugs such as oxaliplatin can decrease in the presence of β-cryptoxanthin to achieve same percentage of growth inhibition.…”
Section: Bioactivity and The Protective Effects Of Natural Carotenmentioning
confidence: 99%
See 1 more Smart Citation
“…A very recent human intervention study [ 62 ] focused on the therapeutic potential of β-cryptoxanthin individually and in combination with oxaliplatin in colon cancer: β-cryptoxanthin decreased the proliferation of cancer cells and cooperated with oxaliplatin to induce apoptosis through the negative regulation of NH 2 -terminally truncated p73 (ΔNP73). The administration of anti-tumoral drugs such as oxaliplatin can decrease in the presence of β-cryptoxanthin to achieve same percentage of growth inhibition.…”
Section: Bioactivity and The Protective Effects Of Natural Carotenmentioning
confidence: 99%
“…The combined regimen produced greater benefits than either individual modality, without increasing side effects. Additionally, the concentration-limiting toxicity of oxaliplatin is reduced in presence of this antioxidant carotenoid [ 62 ].…”
Section: Bioactivity and The Protective Effects Of Natural Carotenmentioning
confidence: 99%
“…β-Cryptoxanthin has been reported to decrease lung cancer through downregulating neuronal nicotinic acetylcholine receptor α7/PI3K signaling pathway [75]. In addition to lung cancer, β-cryptoxanthin enhances the action of a chemotherapeutic agent, oxaliplatin, to treat colon cancer [76]. Moreover, high lycopene and β-cryptoxanthin including diet might protect against aggressive prostate cancer [77].…”
Section: Antioxidant Functions Of Carotenoids At Molecular Level For mentioning
confidence: 99%
“…However, recent in vitro, in vivo, and human-intervention studies report that β-cryptoxanthin can differentially regulate the expression of P73 variants. In addition, these studies have found that this carotenoid has the ability to inhibit the proliferation of colon cancer cells and in conjunction with oxaliplatin, can induce apoptosis in cancer cells by negatively regulating ΔNP73 [ 111 ].…”
Section: Carotenoids and Their Biological Activitiesmentioning
confidence: 99%